Modeling the Improvement of the Technology Transfer Process in Iran's Petro-Refining Industry Using a System Dynamics Approach - Esmaeili, Mansoureh; Movahhedi, Mohammad Mehdi; Motamedi, Majid (Digital Transformation and Administration Innovation, 2025)
The main objective of this research is to model the technology transfer process in Iran's petro-refining industry using the system dynamics method in order to improve this process. This analysis assists decision-makers in identifying critical success factors and designing optimization strategies for the technology transfer process. Following the system dynamics approach, this study investigates the dynamics of variables affecting the development and improvement of the technology transfer process in Iranian petro-refineries through a review of relevant studies and interviews with industry experts. Eight subsystems were identified in this study: organizational and environmental infrastructures, technology monitoring and selection, technology acquisition, technology learning and localization, knowledge management, innovation system, technology development and improvement, and technology dissemination. The causal loop diagrams associated with these subsystems were developed using Vensim software. Ultimately, the analysis of the causal loop diagrams indicates that the primary enabler for optimal technology transfer in Iranian petro-refineries is the existence of an organizational body dedicated to the leadership, coordination, and control of the technology transfer process. The absence of such an organization will hinder the optimal completion of the technology transfer process.